2021
DOI: 10.1007/s12035-021-02574-9
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxicity and Glioprotection: the Dual Role of Glial Cells

Abstract: Glial cells (astrocytes, oligodendrocytes and microglia) are critical for the central nervous system (CNS) in both physiological and pathological conditions. With this in mind, several studies have indicated that glial cells play key roles in the development and progression of CNS diseases. In this sense, gliotoxicity can be referred as the cellular, molecular, and neurochemical changes that can mediate toxic effects or ultimately lead to impairment of the ability of glial cells to protect neurons and/or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 204 publications
(203 reference statements)
1
23
0
1
Order By: Relevance
“…In line with this, there is now emerging evidence that both the progression and clinical outcomes of Zika infection are closely associated with glial cells (Greenhalgh et al, 2020;Quincozes-Santos et al, 2021). Glial cells are essential for brain development and homeostasis (Greenhalgh et al, 2020).…”
Section: Immune and Inflammatory Mechanismsmentioning
confidence: 89%
“…In line with this, there is now emerging evidence that both the progression and clinical outcomes of Zika infection are closely associated with glial cells (Greenhalgh et al, 2020;Quincozes-Santos et al, 2021). Glial cells are essential for brain development and homeostasis (Greenhalgh et al, 2020).…”
Section: Immune and Inflammatory Mechanismsmentioning
confidence: 89%
“…Several studies have shown that, despite causing injury, inflammation also maintains the balance of physiological responses in the body [ 61 ]. In addition, while certain neuroinflammatory pathways are destructive, they can also repair cerebral ischemic damage [ 62 ]. After I/R injury, inflammation typically occurs in three phases: i.e., acute, subacute, and chronic phases.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia are motile cells that investigate the brain environment. Upon brain invasion or insult, microglia quickly develop into different functionally overlapping phenotypes to exert neuroprotective and neurotoxic effects [54]. Phagocytic microglia are the first cells activated upon bilirubin insult [17,46,55], in an attempt to protect neurons from injury by suppressing the inflammatory response, clearing harmful substances and removing cellular debris.…”
Section: Yin-yang Properties Of Neuroinflammation In Bilirubin Neurot...mentioning
confidence: 99%